2007
DOI: 10.1590/s0100-69912007000300008
|View full text |Cite
|
Sign up to set email alerts
|

Influência do baço, da asplenia e do implante esplênico autógeno no metabolismo lipídico de camundongos

Abstract: OBJETIVO: Estudar a influência do baço, da asplenia e do implante esplênico autógeno no metabolismo lipídico, por meio da avaliação do lipidograma sérico de camundongos e da verificação do efeito do transplante autógeno de baço em diferentes locais do abdome. MÉTODO: Foram utilizados camundongos BALB/c distribuídos em sete grupos de 10 animais: controle normal (CN); controle obeso (CO); operação simulada (OS); esplenectomia total (ET); três grupos submetidos ao transplante autógeno do baço: omento maior (OM), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 27 publications
(29 reference statements)
0
7
0
Order By: Relevance
“…Rezende et al 14 , who suggested that the spleen does not seem to participate in the regulation of plasma lipid levels in BALB/c mice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rezende et al 14 , who suggested that the spleen does not seem to participate in the regulation of plasma lipid levels in BALB/c mice.…”
Section: Discussionmentioning
confidence: 99%
“…Study by Rezende et al 14 showed that splenectomy in BALB/c mice did not increase plasma lipid fractions. These authors suggested that spleen does not participate in plasma lipids levels regulation in the herein studied mice strain.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…When comparing the current study with published results for the autologous implants of ovaries and spleen, it is noteworthy that the histological structures of different endocrine organs behave in different ways for the implant without vascular anastomosis 23 . Marc Luetjens et al 5 and Pettersson et al 6 observed that, regardless of where the ovaries were implanted, the maintenance of their histological and endocrine structure is a rule in autogenous implants [5][6] .…”
Section: Discussion Discussion Discussion Discussionmentioning
confidence: 76%
“…Meanwhile, in six other studies, there was no change at all in the lipid pro les 9 23, 24, 25, 26, 27 . However, atherosclerosis was seen more frequently in three of these studies 9,23,24 the incidence did not change in two of them 26,27 and interestingly, atherosclerosis was found less frequently in the study conducted by Li et al 25 . Furthermore, Akan 12 and Lemos-Paulo 28 found that all lipid parameters increased after splenectomy; while Akan 12 found that their levels returned to normal with autotransplantation.…”
Section: Discussionmentioning
confidence: 89%